Environmental, social and governance (ESG): uma análise na perspectiva da sensibilidade da remuneração executiva ao desempenho de mercado - Grodt, Jonas Adriel dos Santos (2022)
Environmental, Social and Governance (ESG) investments have gained emphasis in the corporate sphere and can be considered strategic investments for organizations, even impacting executive compensation. Based on agency theory, stakeholder theory and good governance view, this research aims to investigate the moderating effects of the level of ESG disclosure on executive compensation sensitivity to market performance (pay-performance sensitivity) in Brazilian companies listed in the IBrX-100 Index of Brasil, Bolsa, Balcão (B3 S/A) from 2016 to 2021. The research is classified as quantitative, descriptive and documentary. The data were obtained from the available databases of Economática® and Refinitiv Eikon®, as well as from information contained in the Reference Forms made available on the B3 website. Data analysis was performed, for an amount of 81 companies, based on panel data regression. The method used for the main analysis was the Ordinary Least Squares (OLS) regression model, while for a sensitivity/robustness analysis, quantile regression was used. Findings reveal a positive and significant relationship between the market value of companies and executive compensation, this result indicates the existence of pay-performance sensitivity for the companies in the sample. Regarding the direct effect of the ESG disclosure level (general and its pillars) on executive compensation, in general, ESG and the environmental and social pillars reveal a negative and significant relationship with executive compensation, factors that help to explain the decrease in executive pay. Regarding the moderating effect of the ESG disclosure level on the sensitivity of executive compensation to market performance, the results reveal a positive and significant relationship between the interactive variable and executive compensation, which means these findings reveal that the level of ESG disclosure and its pillars (environmental, social and governance) have the potential to intensify the sensitivity of executive compensation to companies’ market performance. It is concluded that the ESG disclosure level can be a mechanism used to align interests between shareholders and executives. This score has an informational character and its effects can be supported by the stakeholder theory and good governance view in the Brazilian context. This study contributes to the literature by bringing new evidence on pay-performance sensitivity and identifying which theoretical perspective supports the findings. It contributes to organizational practices by providing empirical evidence that ESG investments can mitigate agency problems, encouraging a new management style. Contributes to society by encouraging organizations to invest in environmental, social and governance aspects, which positively impact the community.